Corneal Biomechanical Assessment Using Corneal Visualization Scheimpflug Technology in Keratoconic and Normal Eyes - Lei Tian; Yi-Fei Huang; Li-Qiang Wang; Hua Bai; Qun Wang; Jing-Jing Jiang; Ying Wu; Min Gao (Journal of Ophthalmology)
Purpose. To compare the corneal biomechanical properties of keratoconic patients and age-matched controls using corneal visualization Scheimpflug technology (Corvis ST). Methods. Sixty keratoconic eyes from 47 keratoconus patients and 60 normal eyes from 60 controls were enrolled in this prospective study. Tomography and biomechanical parameters of all eyes were obtained with the Pentacam and Corvis ST, respectively. Intraocular pressure was measured using a Goldmann applanation tonometer. Results. The tomography and biomechanical parameters of the keratoconic corneas were significantly different from those of the normal corneas except for the anterior chamber angle, first applanation length, the highest concavity time, and peak distance. The deformation amplitude was the best predictive parameter (area under the curve: 0.882), with a sensitivity of 81.7%, although there was a significant overlap between keratoconic and normal corneas that ranged from 1.0 to 1.4 mm. In both the keratoconus and control groups, the deformation amplitude was negatively correlated with intraocular pressure, central corneal thickness, and corneal volume at 3 and 5 mm. Conclusions. Corvis ST offers an alternative method for measuring corneal biomechanical properties. The possibility of classifying keratoconus based on deformation amplitude deserves clinical attention.